The Aachen Rail Shuttle ARS - Autonomous and energy self-sufficient feeder transport. (March 2022) - Schindler, Christian
Abstract: This article is about a research and development project that deals with the rail bus of the 3rd generation. The vehicle concept is aimed to be energyself-sufficient and locally emission free. It has the dimensions of a standard city road bus and is designed to operate autonomously on sight in rural areas. The Aachen Rail Bus (ARS) is intended to provide a significantly better service by shorter headways in order to attract more passengers from the countryside to the rail. The research challenges are to prove that the ARS can operate at line of sight, that the energy storage system is suitable for the proposed operation concept and that the passive safety system protects the light and relatively weak passenger compartment, which shall be easily exchangeable by an adequate interface to the chassis that includes all technical equipment. Highlights: driverless operation. lightweight. batterie powered. rural area operation.